Configuring knowledge in practice-grounded research networks: a Contemporary Example - Partington, David; Young, Malcolm (Cranfield University, 2002)
Management scholars have an opportunity to play two important roles in helping to address the practice-grounded management research agenda. First, they are wellplaced to act as cross-sector integrators of management knowledge within networks of organizations which are faced with similar management problems but which are otherwise dissimilar and unconnected. Second, they potentially have access to a wide range of advanced or specialized research skills, in particular the development and application of innovative quantitative and qualitative methods to new problems. In this paper we describe a research initiative that aims to combine these two roles in the pursuit of knowledge about the characteristics of competent strategy implementers. Taking the perspective of strategic programs, we highlight important theoretical differences between programs and rationalistic, reductionist, generic approaches to project management which, for many management professionals, are the principal source of program management knowledge. We argue that a variant of the interpretive research approach known as phenomenography may be combined with traditional, rigorous grounded theorizing to answer important practically-oriented questions about program management competence, with the ultimate aim of generating useful knowledge about the selection and development of strategic program managers in contrasting contexts.
Keywords: Mode 2 research; strategy implementation; phenomenography